Evaluation of the in vitro antioxidant, cytotoxic and genotoxic/antigenotoxic effects of resveratrol - Taner, Gökçe; Aydin, S.; Aytac, Z.; Basaran, A. A.; Basaran, N. (Elsevier Ireland Ltd, 2016)
[No Abstract Available]
52nd Congress of the European-Societies-of-Toxicology (EUROTOX) -- SEP 04-07, 2016 -- Seville, SPAIN
Keywords: [No Keywords]